Numerical simulation on the effectiveness of using viscoelastic materials to mitigate seismic induced vibrations of above-ground pipelines - Bi, Kaiming; Hao, Hong (Pergamon, 2016)
Pipeline systems are commonly used to transport oil, natural gas, water, sewage and other materials. They are normally regarded as important lifeline structures. Ensuring the safety of these pipeline systems is crucial to the economy and environment. There are many reasons that may result in the damages to pipelines and these damages are often associated with pipeline vibrations. Therefore it is important to control pipeline vibrations to reduce the possibility of catastrophic damages. This paper carries out numerical investigations on the effectiveness of using viscoelastic materials to mitigate the seismic induced vibrations of above-ground pipelines. The numerical analyses are carried out by using the commercial software package ANSYS. The numerical model of the viscoelastic material is firstly calibrated based on the experimental data obtained from vibration tests of a 1.6 m long tubular sandwich structure. The calibrated material model is then applied to the above-ground pipeline system. The effectiveness of using viscoelastic materials as the seismic vibration control solution is investigated. The influences of various parameters, including the constraining arrangement scenarios, the constraining length and angle, the thicknesses of the viscoelastic material and constraining layer are discussed in detail. The influence of earthquake frequency content is discussed as well. Numerical results show that with properly selected viscoelastic materials and constraining layers, the proposed method can be used to effectively mitigate seismic induced vibrations of above-ground pipelines.